Teaching Creative Thinking Skills with Laboratory Work - Nur Khoiri; Slamet Riyadi; Ummi Kaltsum; Nathan Hindarto; Ani Rusilawati (Universitas Sebelas Maret, 2017)
Research on figuring out the ways to teach creative thinking skills via learning processes has been carried out. One of the methods applied to be efficient to teach creative thinking skills is laboratory work. Laboratory work is an important process in learning physics since students tend to find it hard to understand physical concepts if they are only taught verbally. Students will understand better when they are given real life examples and are allowed to learn the concepts through the laboratory work, whenever possible. The research was conducted at SMAN 1 Bringin by employing the quasi-experiment pre-test - post-test control group design. Creative thinking skills were measured based on four indicators: flexibility, fluency, originality, and detail. Results show that laboratory work was suitable to improve students’ fluent thinking ability with 77% students showing improvement, and it was also a fit to improve students’ original thinking with 84% students showing improvement. The experiment class revealed a gain of 0.51, taken from an average pre-test score of 45.64 compared to the average post-test score of 73.5, which is an increase of 27.86. Meanwhile, the control class resulted in a gain of 0.40, taken from an average pre-test score of 39.11 compared to the average post-test score of 83.44, which is an increase of 24.33.